DEVELOPMENT OF A SIMPLE LABORATORY-SCALE LANDSLIDE SIMULATION SYSTEM USING A SHAKING TABLE AND ARTIFICIAL RAINFALL - Elfi Yuliza; Muhammad Khafid Fauzi; Riska Ekawita; Refrizon Refrizon (Universitas Mataram, 2026)
A landslide mitigation system is essential to reduce the potential risks of disasters. Historical records of both localized and widespread landslide events indicate that the development of sensor-based early warning systems is an effective approach. The design of such systems requires an understanding of landslide characteristics and sensor response to physical changes in soil. Therefore, this study developed a laboratory-scale landslide simulation model to investigate landslide behaviors. The model incorporates two primary triggering factors, namely vibration and A landslide mitigation system is essential to reduce the potential risks of disasters. Historical records of both localized and widespread landslide events indicate that the development of sensor-based early warning systems is an effective mitigation approach. The design of such systems requires an understanding of landslide characteristics and sensor responses to physical changes in soil. Therefore, this study developed a simple laboratory-scale landslide simulation system integrating a shaking table, an artificial rainfall, and a sensor system. The novelty of this work lies in integrating two different triggering factors, vibration through a shaking table and rainfall, using artificial rainfall. Two different materials, laterite and soil, were used to obtain ground movement characteristics. The results indicate that each material responded differently to the applied triggering factors. Laterite soil with clayey characteristics became soft and exhibited plasticity behavior under wet conditions and hardened under dry conditions. Consequently, vibration-induced movement in zones with weak soil bonding, while the addition of water primarily caused fluid flow associated with rainfall. In contrast, for sand samples, both vibration and artificial rainfall reduced pore size and enhanced soil bonding. However, an optimal pore size was observed, as excessive saturation led to fractures and collapse. Excess water also promotes fluid flow and liquefaction. Furthermore, the sensor system effectively detected and responded to the observed changes during the experimental procedure.